2021
DOI: 10.1038/s41467-021-25325-9
|View full text |Cite
|
Sign up to set email alerts
|

MiR-205-driven downregulation of cholesterol biosynthesis through SQLE-inhibition identifies therapeutic vulnerability in aggressive prostate cancer

Abstract: Prostate cancer (PCa) shows strong dependence on the androgen receptor (AR) pathway. Here, we show that squalene epoxidase (SQLE), an enzyme of the cholesterol biosynthesis pathway, is overexpressed in advanced PCa and its expression correlates with poor survival. SQLE expression is controlled by micro-RNA 205 (miR-205), which is significantly downregulated in advanced PCa. Restoration of miR-205 expression or competitive inhibition of SQLE led to inhibition of de novo cholesterol biosynthesis. Furthermore, SQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 58 publications
2
48
0
1
Order By: Relevance
“…Therefore, therapeutics that suppress elevated intratumoral cholesterol levels without induction of the feedback response are optimal strategies. Recently, drugs or compounds such as ezetimibe that target NPC1L1 protein for blocking cholesterol absorption and terbinafine that can inhibit SQLE were shown to be effective in inhibition of PCa tumor growth [9,21], thus supporting the notion that targeting the tumor aberrant cholesterol homeostasis can be an attractive option.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, therapeutics that suppress elevated intratumoral cholesterol levels without induction of the feedback response are optimal strategies. Recently, drugs or compounds such as ezetimibe that target NPC1L1 protein for blocking cholesterol absorption and terbinafine that can inhibit SQLE were shown to be effective in inhibition of PCa tumor growth [9,21], thus supporting the notion that targeting the tumor aberrant cholesterol homeostasis can be an attractive option.…”
Section: Introductionmentioning
confidence: 95%
“…Notably, studies have demonstrated that both cholesterol biosynthesis and efflux are reprogrammed in mCRPC, which may be major contributors to tumor growth and lethal progression [6][7][8]. Indeed, elevated expression of cholesterol biosynthesis rate-limiting enzymes such as SQLE have been strongly correlated with poor outcome of PCa [7,9,10]. Low or loss of expression of key efflux proteins such as ABCA1 and metabolic enzymes such as CYP27A1 are also associated with the disease progression [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant SM expression and activity is an emerging hallmark of numerous malignancies [21, 53], yet the contribution of the constitutively active trunSM to oncogenesis is unknown. Therefore, we performed immunoblotting of paired tumor and adjacent benign tissue lysates from cohorts of lean and obese endometrial cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…For example, VEGFR2 was shown to mark PCa cases with a high risk of progression ( 30 , 66 ). In addition, angiogenesis-related microRNAs such as let-7, miR-195 and miR-205 ( 67 ) are also deregulated and play prominent roles in PCa ( 68 70 ). However, no angiogenesis-specific inhibitor has met its clinical endpoint in phase III trials (see Figure 1A ).…”
Section: Discussionmentioning
confidence: 99%